Comparative Analysis of Hand Hygiene Discipline Based on Gender Among Practical Students in The Laboratory of Universidade Da Paz - Noelio Auxilio Pedro Martins (Lembaga Teewan Journal Solutions, 2026)
This study was motivated by the importance of hand hygiene as a fundamental infection prevention measure in health education laboratory settings, where student compliance may be influenced by several factors, including gender. The aim of this study was to analyze differences in hand hygiene compliance based on gender among practical students at the Laboratory of Universidade da Paz, Timor Leste. This research used a quantitative comparative design. The sample consisted of 100 students, including 50 males and 50 females from the odd semester. Data were collected through hand hygiene compliance observation and analyzed using the Pearson Chi-Square test. The results showed that most respondents were in the compliant category (89%), with female students demonstrating higher compliance (92%) compared to male students (86%). However, statistical analysis revealed no significant difference between gender and hand hygiene compliance, with a p-value of 0.469 (>0.05). The conclusion of this study is that there is no significant difference in hand hygiene compliance based on gender among practical students, indicating that compliance behavior is more influenced by learning environment, habituation, and supervision in laboratory settings.